Answer:
d. 4x^2 +24x +23
Explanation:
Evaluating polynomials is sometimes easier when they are written in Horner form:
f(x) = (4x +8)x -9
Substituting (x+2) for x, we have ...
f(x+2) = (4(x+2)+8)(x+2) -9
= (4x +16)(x +2) -9
= 4x^2 +24x +32 -9
= 4x^2 +24x +23 . . . . . matches choice D
_____
Alternative method
You can observe that the answer choices differ in the coefficient of the x-term. So, to make the correct selection, you only need to find the coefficient of the x-term. That will be the sum of coefficients of the x-terms in 4(x+2)^2 and 8(x+2). Those x-terms are 4·4x and 8x, so have a sum of (16+8)x = 24x. This matches choice D.